New myths of OZ: the Australian beach and the negotiation of national belonging by refugee background youth. Issue 1 (2nd January 2016) - Lems, Annika; Gifford, Sandy; Wilding, Raelene
Abstract : In this article, we consider the Australian beach as a material, imaginary and social arena in which different versions of national belonging are performed and contested. Focusing on two short films produced by young people from refugee backgrounds, we explore the negotiation of national belonging on the beach by people who occupy identity categories that are typically excluded from idealizing Australian beach mythologies. We argue that both the production and distribution of these films contribute to a reimagining of the Australian beach that creates new opportunities for people from migrant backgrounds to engage in the co-production of Australian identities in their own terms.